Spaces of masculinities - Hoven, Bettina van; Hörschelmann, Kathrin, 1971- (Critical geographies ;, 2005)
Drawing on a variety of geographical research projects, the central concern of this book is to highlight the significance of research about masculinity in sociological and geographical work dealing with constructions of gender.